IMPLEMENTASI MODEL PICTURE AND PICTURE BERBASIS TEKNOLOGI UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Faizatul Widat; Nur Endah Dian Rosyadani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and study the implementation of technology-based picture and picture models to increase students' interest in learning at Madrasah Ibtidaiyah. This is done to assist teachers in carrying out learning so that students' interest in learning can increase. The researcher uses a qualitative approach with a case study type. The research was conducted at MINU 19 Tanjung Anyar. The results of the study show that the application of the technology-based picture and picture model can increase students' interest in learning. Its implementation is carried out in several stages, namely: first, planning. Second, implementation. Third, evaluation. The application achieved using this model makes students show an increase in interest in learning which can be seen from their active involvement during learning, such as their increased attention, participation, and enthusiasm in participating in learning activities.